2017
DOI: 10.1002/adem.201600632
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Mechanical and Tribological Behavior of dcMS/HPPMS CrN and (Cr,Al)N Hard Coatings Using Nanoscratch Technique

Abstract: In this paper, interfacial adhesion strength and tribological behavior of systems, consisting of CrN and (Cr,Al)N coatings and AISI 420 steel substrate are investigated. The coatings are deposited using a hybrid technology consisting of direct current and high power pulse magnetron sputtering dcMS/HPPMS. Conventional Rockwell and scratch tests as well as nanoscratch analyses are performed. For the nanoscratch tests, a Berkovich and a conical indenters are used. Damage mechanisms are analyzed using Scanning Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…A constant Poisson's ratio of υ = 0.25 was assumed for the coatings according to the previous work . In addition, the plastic work W pl and elastic work W el were determined from the nanoindentation force–displacement curves according to the previous work, to determine the ratio of plastic work to total work W pl / W total . The lower the ratio, the greater is the resistance to plastic deformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A constant Poisson's ratio of υ = 0.25 was assumed for the coatings according to the previous work . In addition, the plastic work W pl and elastic work W el were determined from the nanoindentation force–displacement curves according to the previous work, to determine the ratio of plastic work to total work W pl / W total . The lower the ratio, the greater is the resistance to plastic deformation.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, there is an effort to combine TMD with a wear‐resistant hard phase to provide resistance to abrasive wear combined with friction reduction. The ternary coating system (Cr,Al)N deposited by PVD is a promising candidate for this purpose as it exhibits a high hardness, good abrasion wear resistance and high corrosion resistance . These coating systems can be deposited with PVD technologies such as direct current magnetron sputtering (DCMS) or high‐power pulsed magnetron sputtering (HPPMS).…”
Section: Introductionmentioning
confidence: 99%
“…The four force-displacement curves analyzed show no distinct drop-ins, which would have indicated the formation of cracks underneath the indenter. As suggested in [12], since significant crack formation can therefore be neglected, an increased relative elastic work (W el /(W pl + W el )) can be interpreted as a higher resistance against plastic deformation.…”
Section: Coating Characterizationmentioning
confidence: 96%
“…Investigations using scratch and Rockwell impact tests have shown that even brittle nitride coatings undergo plastic deformation not only under hydrostatic, concentrated loads as in indentation, but also under similar but dynamic loading conditions. The adhesion behaviour between coating and substrate can also be investigated in this way [12,[48][49][50][51], but several studies suggest that the mechanical properties of the coating, the tribological behaviour and the substrate/coating interface are interrelated [32,52]. For example, high resistance to plastic deformation also leads to improved abrasion resistance at the substrate/coating interface [52].…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion behaviour between coating and substrate can also be investigated in this way [12,[48][49][50][51], but several studies suggest that the mechanical properties of the coating, the tribological behaviour and the substrate/coating interface are interrelated [32,52]. For example, high resistance to plastic deformation also leads to improved abrasion resistance at the substrate/coating interface [52]. To guide materials and process design, it is therefore important to characterise the coating itself, ideally revealing also the different possible fracture mechanisms individually with their respective critical stresses.…”
Section: Introductionmentioning
confidence: 99%